2013
DOI: 10.3390/rs5041894
|View full text |Cite
|
Sign up to set email alerts
|

On the Variation of NDVI with the Principal Climatic Elements in the Tibetan Plateau

Abstract: Temperature and precipitation have been separately reported to be the main factors affecting the Normalized Difference Vegetation Index (NDVI) in the Tibetan Plateau. The effects of the main climatic factors on the yearly maximum NDVI (MNDVI) in the Tibetan Plateau were examined on different scales. The result underscored the observation that both precipitation and temperature affect MNDVI based on weather stations or physico-geographical regions. Precipitation is the main climatic factor that affects the vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 33 publications
3
86
0
2
Order By: Relevance
“…However, the NDVI of the alpine desert steppe rose first and then declined sharply, but in recent years, the vegetation cover of the alpine desert steppe gradually became better and better. The same change tendency of NDVI was demonstrated in the study region (Sun et al 2013b). Moreover, our result is in line with the report of Shen et al (2014), which suggested that the mean maximum enhanced vegetation index (EVI) also showed an insignificant decreasing trend over the entire Tibetan Plateau.…”
Section: Spatiotemporal Changes Of Ndvisupporting
confidence: 91%
See 3 more Smart Citations
“…However, the NDVI of the alpine desert steppe rose first and then declined sharply, but in recent years, the vegetation cover of the alpine desert steppe gradually became better and better. The same change tendency of NDVI was demonstrated in the study region (Sun et al 2013b). Moreover, our result is in line with the report of Shen et al (2014), which suggested that the mean maximum enhanced vegetation index (EVI) also showed an insignificant decreasing trend over the entire Tibetan Plateau.…”
Section: Spatiotemporal Changes Of Ndvisupporting
confidence: 91%
“…To remove noise from the remote sensing data caused by clouds or weather, the maximum value composite (MVC) method was used as one step in the process. Over the past 32 years, the linear trend coefficient was used to identify the changed tendencies of annual maximum NDVI and climate factors (MAT and MAP) (Sun et al 2013b).…”
Section: Datasets and Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As temperature has increased in China over the past three decades, the stimulation of vegetation growth due to temperature has gradually diminished, and the weakening positive impacts of climate warming on vegetation growth may be partly related to warming-induced soil drying (Trenberth et al, 2007;Piao et al, 2010Piao et al, , 2014Dai, 2011;Peng et al, 2011;Fu et al, 2013) causing by increasing evaporation (Sun et al, 2013). Previous studies have suggested that although warming could enhance forest vegetation growth in South China (Peng et al, 2011), drought has become more common since the 1970s, especially in the tropics and subtropics, and the effect of drought can attenuate the response of NDVI to temperature (Piao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%